Differential vascular effects of aspirin in people with Type 2 diabetes without cardiovascular disease and matched controls without diabetes. Issue 9 (11th May 2019) - Vernstrøm, L.; Laugesen, E.; Grove, E. L.; Baier, J. M.; Gullaksen, S.; Hvas, A.‐M.; Poulsen, P. L.; Funck, K. L.
Abstract: Aim: We investigated whether the effect of low‐dose aspirin on endothelium‐dependent vasodilation and arterial stiffness in people with Type 2 diabetes is different from a matched control group. We examined acute and chronic effects, and effects over the 24h dosing interval. Methods: In an open‐label parallel group intervention study, we included 21 participants with Type 2 diabetes and 21 age‐ and sex‐matched controls. Endothelium‐dependent vasodilation was assessed as the reactive hyperaemia index (lnRHI) measured by peripheral arterial tonometry (EndoPAT ® ). Arterial stiffness was assessed as pulse wave velocity (PWV) measured by applanation tonometry (SphygmoCor ® ). Measurements were performed prior to aspirin intake and 1h after aspirin administration (75 mg). Participants were then treated for 6 days, and measurements were repeated at 24 h and 1 h after aspirin intake. Results: Baseline lnRHI did not differ between groups. The controls had an immediate increase in lnRHI after the first aspirin tablet. This was not observed in participants with diabetes (difference between groups; P < 0.05). After 1 week, both groups demonstrated increased lnRHI compared with baseline ( P < 0.01). In participants with diabetes, lnRHI was significantly lower 24 h after aspirin administration compared with 1 h after administration ( P < 0.05). This difference was not observed in controls ( P = 0.84, difference between groups; P = 0.12). The effect on PWV did not differ between groups. Conclusion: Aspirin had a reduced immediate effect on endothelium‐dependent vasodilation in participants with diabetes. Both groups had improved endothelial function after 1 week of treatment. Further, the effect of aspirin on endothelial function may be declining during a 24 h dosing interval in people with Type 2 diabetes. (Clinical Trial Registry No: 2016‐000515‐32) What's new?: Aspirin has been shown to improve endothelial function and reduce arterial stiffness in people without diabetes. Participants with Type 2 diabetes had a reduced immediate effect of the first administered aspirin dose on endothelial function. The effect of aspirin on endothelial function seems to decline during the dosing interval in participants with Type 2 diabetes. These findings may represent an early sign of endothelial dysfunction in people with Type 2 diabetes who may benefit from twice‐daily dosing of aspirin.